Critical THI thresholds based on the physiological parameters of lactating dairy cows. (February 2020) - Pinto, Severino; Hoffmann, Gundula; Ammon, Christian; Amon, Thomas
Abstract: The severity of heat stress conditions in high-yielding dairy cows is currently underestimated. The present study aimed to determine the heat load threshold of the temperature-humidity index (THI) on physiological parameters of lactating Holstein-Friesian cows under a continental climatic zone in Germany. Physiological parameter measurements, such as respiration rate (RR), measured hourly, and heart rate (HR) and rectal temperature (RT), both measured twice daily, were performed in a total of 139 multiparous cows on three randomly chosen measurement days per week. In addition, the ambient temperature and relative humidity of the barn were recorded every 5 min to calculate the current THI. The physiological parameter data were linked to the THI, and the heat load thresholds were determined using the broken-stick model. The heat load duration effect of each physiological parameter was obtained by regression analysis. Considering the increases in the physiological parameters, our study provided reliable data to determine heat load thresholds for lactating high-yielding dairy cows in a moderate climatic zone. The heat load threshold could be determined for RR in standing cows (THI = 70) and lying cows (THI = 65) and for HR (THI = 72) and RT (THI = 70) in standing cows. The heat load duration also demonstrated a significant effect on the increases in physiological parameters among dairy cows. In particular, the present study enabled a strategy to be devised to initiate heat mitigation in high-yielding dairy cows when they are exposed to THIs above 65. Highlights: Detection of heat load by monitoring the physiological parameters of dairy cows. Body postures influenced the heat load threshold for respiration rate of cows. Lying cows demonstrated lower heat load threshold of 65 THI for respiration rate. Heat load threshold of 69 THI for heart rate in standing cows. Standing cows demonstrated heat load threshold of 70 THI for rectal temperature.